2014
DOI: 10.1371/journal.pone.0107244
|View full text |Cite
|
Sign up to set email alerts
|

Common Genetic Variants of the Human Steroid 21-Hydroxylase Gene (CYP21A2) Are Related to Differences in Circulating Hormone Levels

Abstract: PurposeSystematic evaluation of the potential relationship between the common genetic variants of CYP21A2 and hormone levels.MethodsThe relationships of CYP21A2 intron 2 polymorphisms and haplotypes with diverse baseline and stimulated blood hormone levels were studied in 106 subjects with non-functioning adrenal incidentaloma (NFAI). The rationale for using NFAI subjects is dual: i) their baseline hormone profiles do not differ from those of healthy subjects and ii) hormone levels after stimulation tests are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
(67 reference statements)
0
10
1
1
Order By: Relevance
“…Although 21-DF is a known marker of 21-hydroxilase deficiency, in our SH patients several aspects, such as low ACTH, increased basal and stimulated F, and 17-OHP values comparable with NS adenomas, argue against this possibility. Our results are in contrast with previous studies highlighting some degrees of dysregulation of CYP21 in adrenocortical adenomas (37,38). The main reason for this difference relies on the different methods of 17-OHP determination, which are not comparable with our highly accurate LC-MS/MS.…”
Section: Discussioncontrasting
confidence: 99%
“…Although 21-DF is a known marker of 21-hydroxilase deficiency, in our SH patients several aspects, such as low ACTH, increased basal and stimulated F, and 17-OHP values comparable with NS adenomas, argue against this possibility. Our results are in contrast with previous studies highlighting some degrees of dysregulation of CYP21 in adrenocortical adenomas (37,38). The main reason for this difference relies on the different methods of 17-OHP determination, which are not comparable with our highly accurate LC-MS/MS.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, in studies of patients with uni-or bilateral adrenal adenomas, 16 % were CYP21A2 carriers and 2-6 % had undiagnosed CAH [179][180][181][182]. In contrast, others have only found 0.5 % of the patients with adrenal incidentalomas to be affected by CAH [183], and some have reported that their finding of 9.6 % CYP21A2 carriers with nonfunctioning adrenal incidentaloma was not different from that in healthy controls [184]. How frequently an adrenal incidentaloma presents symptoms of NCAH is unclear, but there are several reports of NCAH diagnoses as the result of the work-up of these tumors [24,29,[180][181][182]185].…”
Section: Adrenal Tumorsmentioning
confidence: 99%
“…For the subjects with the c.955C4T variant, 96 healthy subjects (50% women) from a family study, 21 68 healthy subjects (65.2% women) and 125 patients (76.0% women) with NFAI from a recent study, 22 and 100 patients (58.0% women) with classical CAH due to 21-hydroxylase deficiency from the Second Department of Internal Medicine, Semmelweis University (Budapest, Hungary) and the Second Department of Pediatrics, Semmelweis University (Budapest, Hungary) were screened. In addition, one patient with supposed classical CAH was referred to us by the Department of Pediatrics, University of Pecs (Pecs, Hungary) for reexamination of the original genetic diagnosis.…”
Section: Subjects and Clinical Datamentioning
confidence: 99%
“…The exclusion criteria for NFAI patients were described recently. 22 The diagnosis was confirmed in all CAH patients by hormonal and genetic testing (except for the one who was reexamined) as described. 23,24 Furthermore, 34 adrenocortical tumor specimens of NFAI patients were obtained as described, 25 and screened for the c.955C4T variant.…”
Section: Subjects and Clinical Datamentioning
confidence: 99%